The changing landscape of opioid prescribing: long-acting and extended-release opioid class-wide Risk Evaluation and Mitigation Strategy - Gudin JA (Dove Medical Press, 2012)
Jeffrey A GudinEnglewood Hospital and Medical Center, Englewood, NJ, USAAbstract: Prescriptions for opioid analgesics to manage moderate-to-severe chronic noncancer pain have increased markedly over the last decade, as have postmarketing reports of adverse events associated with opioids. As an unintentional consequence of greater prescription opioid utilization, there has been the parallel increase in misuse, abuse, and overdose, which are serious risks associated with all opioid analgesics. In response to these concerns, the Food and Drug Administration announced the requirement for a class-wide Risk Evaluation and Mitigation Strategy (REMS) for long-acting and extended-release (ER) opioid analgesics in April 2011. An understanding of the details of this REMS will be of particular importance to primary care providers. The class-wide REMS is focused on educating health care providers and patients on appropriate prescribing and safe use of ER opioids. Support from primary care will be necessary for the success of this REMS, as these clinicians are the predominant providers of care and the main prescribers of opioid analgesics for patients with chronic pain. Although currently voluntary, future policy will likely dictate that providers undergo mandatory training to continue prescribing medications within this class. This article outlines the elements of the class-wide REMS for ER opioids and clarifies the impact on primary care providers with regard to training, patient education, and clinical practice.Keywords: long-acting opioid, extended-release opioid, risk, REMS, FDA, primary care